2013
DOI: 10.1103/physrevx.3.041023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Entanglement of Spin Qubits via Ferromagnet

Abstract: We propose a mechanism of coherent coupling between distant spin qubits interacting dipolarly with a ferromagnet. We derive an effective two-spin interaction Hamiltonian and estimate the coupling strength. We discuss the mechanisms of decoherence induced solely by the coupling to the ferromagnet and show that there is a regime where it is negligible. Finally, we present a sequence for the implementation of the entangling CNOT gate and estimate the corresponding operation time to be a few tens of nanoseconds. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
127
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 53 publications
0
127
0
Order By: Relevance
“…Approaches to implementing long-range interactions typically involve identifying a system that acts as a mediator of the interaction between the qubits, with proposed systems including optical cavities and microwave stripline resonators [21][22][23][24][25][26], floating metallic [27] and ferromagnetic [28] couplers, the collective modes of spin chains [29][30][31], superconducting systems [32,33], and multi-electron molecular cores [34]. Recently, long-range coupling of electrons located in the two outer quantum dots of a linear triple dot system has been demonstrated [35,36].…”
mentioning
confidence: 99%
“…Approaches to implementing long-range interactions typically involve identifying a system that acts as a mediator of the interaction between the qubits, with proposed systems including optical cavities and microwave stripline resonators [21][22][23][24][25][26], floating metallic [27] and ferromagnetic [28] couplers, the collective modes of spin chains [29][30][31], superconducting systems [32,33], and multi-electron molecular cores [34]. Recently, long-range coupling of electrons located in the two outer quantum dots of a linear triple dot system has been demonstrated [35,36].…”
mentioning
confidence: 99%
“…Note that the magnon bath considered in Ref. [16] has a dispersion which is parabolic rather than linear, as assumed in this work. For a 2D Ohmic bath (r = 0, D = 2), the function J ij (t) can be calculated as described in Ref.…”
Section: A Bath Coupling As An Entangling Gatementioning
confidence: 99%
“…Recently, the idea of performing entangling gates between qubits by coupling them to an ordered Heisenberg ferromagnet has attracted interest [16]. An ordered Heisenberg ferromagnet can be seen as a 3D magnon bath (ω k = Dk 2 ).…”
Section: Induced Interactions a Linear Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural way to overcome such difficulties is to employ means of entangling spin qubits over long distances, which creates extra space for wiring the quantum circuits. In principle, this may be achieved by coupling the spin qubits to an electromagnetic cavity [7][8][9][10], a floating metallic gate [11], or a dipolar ferromagnet [12]. Recently, it was shown that coupling of distant spin qubits can also be realized via photon-assisted cotunneling [13].…”
Section: Introductionmentioning
confidence: 99%